Pengaruh Persepsi Harga dan Penggunaan Qris Terhadap Loyalitas Konsumen di Coffe Shop : Pada Mahasiswa Bisnis Digital 2023 dan 2024 UPI - Jauza Ulayya; Kyla Annisabia; Reva Fitri Ramadhanti Manitik; Nahira Izzati Ramadhani; Khalista Aurelia; Syti Sarah Maesaroh (Journal Of Business, Finance, and Economics (JBFE), 2025)
The purpose of this research is to determine the influence of price and the use of QRIS transactions on consumer purchase intention at coffee shops (case study on Digital Business students) in 2024 and 2025 at the Universitas Pendidikan Indonesia. The population in this study consists of all Digital Business students from the 2023 and 2024 classes at the Universitas slot thailand Pendidikan Indonesia. The sampling technique used is Probability Sampling, specifically Stratified Random Sampling based on class year. The research instrument is a questionnaire. The data obtained were then processed using analysis with SPSS. The results of this study found that the price (X1) and ease of use (X2) variables have a significant effect on consumer purchase decisions and loyalty (Y).